Literatura japonesa na Biblioteca Mário de Andrade - Albertini, Nicolas Fernando Ferreira (Universidade Federal de São Carlos, 2025)
This research, within the scope of memory, identity and heritage studies, focuses on Japanese literature, which, combined with the collection of the Mário de Andrade Library, constitutes the object of study. Over the years, hundreds of Japanese immigrants have come to Brazil, bringing with them their culture, habits and experiences, resulting in a direct influence on Brazilian society. With the largest concentration in the city of São Paulo, the Japanese community has the Historical Museum of Japanese Immigration in Brazil and a branch of the Japan House. In line with the research's focus on Japanese literature, the collection of the Mário de Andrade Library (BMA) in São Paulo is also of interest. This is because, in addition to being the second largest library in Brazil, it stands out for its mission of disseminating its collection to national and foreign researchers and for its trajectory in the formation of readers and intellectuals. It is in this context that the research question is: How is Japanese literature characterized in the Mário de Andrade Library?, with the aim of analyzing Japanese literature in the collection of this library. The research, with a qualitative approach, is exploratory in its objectives and applied in nature. In order to achieve its objectives, bibliographic and documentary procedures were used to outline the history of the Japanese-Brazilian community and the BMA, and content analysis was used for the results. The data were obtained after being provided by the institution. The study resulted in a proposal to reevaluate the policies for indexing, collections and cataloging the BMA, after analyzing the access points for information resources on Japanese literature. It was concluded that the reformulated application of these policies in the Japanese literature collection of the Mário de Andrade Library will provide new perspectives on the subject, greater visibility of the collection, and make the retrieval of resources more fluid and dynamic.
Japanese literature at the Mário de Andrade Library
Keywords: Literatura japonesa; Biblioteca Mário de Andrade; Comunidade nipo-brasileira; Japanese literature; Mário de Andrade Library; Japanese-brazilian community; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA